Effects of ambient temperature and 37 °C on biological characteristics of processed oligoasthenoteratozoospermic spermatozoa - Sajjad Shahmohammadi; Fatemeh Dehghanpour; Ali Nabi; Moones Vasiee; Mohammad Ali Khalili (Asian Pacific Journal of Reproduction)
Objective: To assess the biological characteristics of human spermatozoa at room temperature (RT, 25 °C) and 37 °C at different time intervals (0, 0.5, 2, and 24 h) post liquefaction. Methods: Twenty oligoasthenoteratozoospermic samples after liquefaction were incubated at 37 °C or RT. Incubation was performed at 4 interval times of 0 (after liquefaction), 0.5, 2, and 24 h. The samples were evaluated for sperm parameters, DNA fragmentation, acrosome reaction, mitochondrial integrity, and lipid peroxidation, at each time interval. Results: After 0.5 h of incubation at RT and 37 °C, there were slight variations in sperm viability, normal morphology and DNA fragmentation. Similarly, mitochondrial integrity, acrosome reaction and lipid peroxidation exhibited slight differences following incubation at 0.5 h at both RT and 37 °C. In addition, the assessed parameters were mostly damaged at 24 h of incubation. The results confirmed that incubation at 37 °C was better than RT in terms of parameters and sperm functional tests, but the difference was not significant. Conclusions: Incubation of oligoasthenoteratozoospermic samples should be done within 0.5 h to minimize the destructive effects of prolonged incubation time (e.g. 24 h) on general and specific sperm parameters. The findings declared that incubation temperature of 37 °C is safer than RT on the biological characteristics of oligoasthenoteratozoospermic processed spermatozoa.